IMPACT OF MULTIPARITY ON IRON CONTENT IN MULTIPAROUS WOMEN - Farooq, Ayesha; Rauf, Shahid; Hassan, Uzma; Sadiq, Naushaba (Journal of Ayub Medical College Abbottabad, 2011)
Background: The effect of multiple pregnancies, a very common pattern in reproductive lifestyle of Pakistani women, needs to be addressed to see if it affects the iron content and hence cause iron deficiency. Recognising this deficiency prior to development of anaemia can prevent disastrous consequences that can complicate the life of the mother and foetus especially in developing countries. The objective of this study was to assess the effect that the stress of multiple pregnancies has on the iron status of the body. Methods: This comparative study was conducted in a focus group of female population. Two hundred subjects were selected by convenient sampling and grouped depending on their parity status. Data regarding diet, and socioeconomic history was collected on pre-designed questionnaire. Serum Ferritin was used to assess iron deficiency using the Electrochemiluminescence Immunoassay (ECLIA). Data was statistically analysed using SPSS-17. Results: Mean value of serum Ferritin in the nulliparous group was 76.52±4.92 Î·g/mL with 16% of nulliparous subjects showing lower than normal values. Thirty-six percent of uniparous subjects showed low serum Ferritin values, mean value being 45.74±4.51 Î·g/mL. Seventy-two percent of the multiparous subjects showed iron deficiency with Ferritin levels of <20 Î·g/mL. Mean serum Ferritin in this group was 25.21±2.75 Î·g/mL. The differences between the Ferritin levels of the study groups were highly significant (p<0.01). Conclusions: Multiparous women had lower serum Ferritin levels than the control group suggesting that the stress of multiple pregnancies takes its toll on the iron content of the body. Keywords: Multiparous, Ferritin, Iron deficiency, Electrochemiiluminescence Immunoassay